Ion dynamics and positron annihilation studies on polymer ceramic composite electrolyte system (PVA/NaClO4/Y2O3): Application in electrochemical devices. Issue 12 (15th June 2022) - Chavan, Chetan; Bhajantri, R.F.; Bulla, Soumya; Ravikumar, H.B.; Raghavendra, M.; Sakthipandi, K.; Yogesh Kumar, K.; Prasanna, B.P.
Abstract: This study aimed to develop a framework to investigate the structural, dielectric, and transport properties of a sequence-based PVA matrix polymer ceramic composite electrolyte system with sodium perchlorate (NaClO4 ) and yttrium oxide (Y2 O3 ) as nanofillers. The XRD results revealed a change in crystallinity. Chemical interactions between the PVA/NaClO4 matrix and yttrium ions were revealed using FTIR studies. From SEM studies, the morphology was observed to be smoother, homogeneous, and coherent for the pure+salt PCCE system after addition of Y2 O3 nanoparticles to the matrix. In Py3% system, the nanoparticles were randomly linearly aligned due to inter- and intramolecular bonding. The elemental composition and mapping were confirmed by the presence of Y2 O3 and NaClO4 particles. For 7 wt%, 1 wt% Y2 O3 nanoparticle loading (Py7%, Py1%) in the PCCE matrix, the positron lifetime parameters o-Ps lifetime (τ3 ) and free volume size ( V f ) showed a minimum (Py7%) and maximum value (Py1%). Between these two values, the value for Py3% was ascertained. It was found that Py3% was least crystalline with highest ionic conductivity 3.25 × 10 −4  S/cm which is strongly influenced by the highest charge concentration ( n ), not its mobility ( μ ). The highest conducting sample (Py3%) had an ion transference number ( t ion ) of 0.919, indicating that the current system was ion-dominant with a small amount of electron participation. The LSV technique determined the potential window for the Py3% PCCE system to be 3 V, indicating that it could be used in energy storage applications. The proposed PCCE system's open circuit voltage was 1.7 V, and the discharge characteristics of a primary sodium battery built with a high-conductivity electrolyte system (Py3%) were thoroughly examined. To ensure the safety of our prepared energy storage systems, we tested films for flame retardancy and dimensional stability. Py3% film demonstrated considerable flame retardation that was stable over several ignitions. Self-extinguishing time for pure+salt displays ⁓ 41 s g −1 whereas in the case of Py3% PCCE it has a value ⁓ 6 s g −1 . Graphical abstract: Image 1